Protection of the Rights of Indonesian Migrant Workers - Triyan Febriyanto; Agus Taufiqur Rohman (Universitas Negeri Semarang, 2018)
To protect migrant workers who work abroad, the government has established Law Number 39 of 2004 concerning Placement and Protection of TKI abroad and its regulations. Nevertheless TKI cannot be protected properly either at the pre -placement stage, when placement (during placement), and after placement (post - placement). Various cases befall migrant workers who work abroad as if they do not know the final word ranging from acts of violence, sexual harassment, wages, working hours, and rest time that is not in accordance with work agreements, and others that violate human dignity and dignity.